Model-based Simulation of VoIP Network Reconfigurations using Graph Transformation Systems - Khan, Ajab; Torrini, Paolo; Heckel, Reiko (Electronic Communications of the EASST, 2009)
We address the modelling and validation of P2P networks withspecial attention for problems related to VoIP services, focusing particularlyon Skype. We use generalised stochastic graph transformation systemsand associated stochastic simulation techniques based on generalised semi-Markov processes.